1998
DOI: 10.1074/jbc.273.28.17445
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of Phosphodiesters through Transformation of the Bacterial Phosphotriesterase

Abstract: The phosphotriesterase from Pseudomonas diminuta catalyzes the hydrolysis of a wide array of phosphotriesters and related phosphonates, including organophosphate pesticides and military nerve agents. It has now been shown that this enzyme can also catalyze the hydrolysis of phosphodiesters, albeit at a greatly reduced rate. However, the enzymatic hydrolysis of ethyl-4-nitrophenyl phosphate (compound I) by the wild-type enzyme was >10 8 times faster than the uncatalyzed reaction (k cat ‫؍‬ 0.06 s ؊1 and K m ‫؍‬… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 31 publications
0
45
1
Order By: Relevance
“…Recent findings that other two metal ion catalysts have promiscuous phosphodiesterase activity provide additional evidence for the inherent catalytic potential of binuclear clusters for catalyzing phosphate diester hydrolysis. The bacterial phosphotriesterase (68), an aminopeptidase from Streptomyces (69), and now alkaline phosphatase have each been shown to provide substantial rate enhancements for cleavage of a phosphate diester bond [(k cat /K m )/k w ) 10 10 - 10 15 ]. As each of these enzymes catalyzes different chemical transformations in their physiological roles and has independent evolutionary histories, this suggests that two metal ions positioned ∼4 Å apart are especially conducive to catalysis of phosphate diester hydrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings that other two metal ion catalysts have promiscuous phosphodiesterase activity provide additional evidence for the inherent catalytic potential of binuclear clusters for catalyzing phosphate diester hydrolysis. The bacterial phosphotriesterase (68), an aminopeptidase from Streptomyces (69), and now alkaline phosphatase have each been shown to provide substantial rate enhancements for cleavage of a phosphate diester bond [(k cat /K m )/k w ) 10 10 - 10 15 ]. As each of these enzymes catalyzes different chemical transformations in their physiological roles and has independent evolutionary histories, this suggests that two metal ions positioned ∼4 Å apart are especially conducive to catalysis of phosphate diester hydrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…A potential physiological phosphodiester substrate for phosphonate monoester hydrolase, however, has not yet been found. An interesting fact is that other binuclear zinc enzymes with an established physiological function, such as aminopeptidase (33), phosphotriesterase (34), and alkaline phosphatase (phosphoric acid monoester hydrolase) (35), also display activity to artificial phosphodiesters (Table IV). Although the activity is orders of magnitude lower as compared with that of ZiPD, this shows that a binuclear zinc active site is preferred for phosphodiester cleavage.…”
mentioning
confidence: 99%
“…While this suggests a role for HocA in phosphate metabolism, it is highly unlikely that the native role is to hydrolyse phosphotriesters, because OPs have only been in existence for the last 50 years. HocA may have evolved from a pre-existing phosphatase or phosphodiesterase as it has been shown that a phosphotriesterase (OPH) could be altered by only one amino acid to possess phosphodiesterase activity (Shim et al, 1998), demonstrating how a minor change can allow a protein to acquire a new activity. Likewise, HocA may have been a pre-existing phosphodiesterase that has acquired phosphotriesterase activity.…”
Section: Discussionmentioning
confidence: 99%